COVID-19, MEDIA BARU DAN RITUAL AGAMA ONLINE - Ikhwan, Saipudin (Qawwam : The Leader's Writing, 2022)
Coronavirus has spread to over 200 countries. To address them, each country adopted similar, similar policies, which limit the interaction and association of people. As a result of the policy, many disrupted public activities have even stopped, one of which is religious activity. Indonesia, with its largest Muslim population, will also be affected. What is more, Indonesia has a wide variety of ethnic and cultural groups and religious denominations. However, to keep religious activity alive during this pandemic, many citizens took advantage of the media of the Internet. As was done by nahdlatul scholars who conducted online distribution via youtube. The article tries to analyze the practice of advanced online presentation by nahdlatul scholars during the pandemic month of Ramadan.